1999
DOI: 10.1128/jvi.73.7.6076-6084.1999
|View full text |Cite
|
Sign up to set email alerts
|

Association of JC Virus Large T Antigen with Myelin Basic Protein Transcription Factor (MEF-1/Purα) in Hypomyelinated Brains of Mice Transgenically Expressing T Antigen

Abstract: Progressive multifocal leukoencephalopathy (PML) is a fatal demyelinating disease caused by cytolytic destruction of oligodendrocytes, the myelin-producing cells of the central nervous system, by the human neurotropic JC virus (JCV). The early protein of JCV, T antigen, which is produced at the early stage of infection, is important for orchestrating the events leading to viral lytic infection and cytolytic destruction of oligodendrocytes. Results from transgenic mouse studies, however, have revealed that, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…As mentioned previously, Purα has the ability to interact with several cellular and viral regulatory proteins. In particular its interaction with the human neurotropic JC virus regulatory protein, T‐antigen, was shown both in vivo in the brains of transgenic mice expressing T‐antigen (Tretiakova et al, 1999) and in vitro in a glial cell culture system (Gallia et al, 1998). As Purα regulates the promoter activity of the gene expressing T‐antigen and by associating with T‐antigen, modulates the activity of this protein, we sought to perform a reciprocal experiment to examine the effect of T‐antigen on the Purα promoter and to determine whether association of T‐antigen and Purα affects the ability of Purα to downregulate the Purα promoter in glial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, Purα has the ability to interact with several cellular and viral regulatory proteins. In particular its interaction with the human neurotropic JC virus regulatory protein, T‐antigen, was shown both in vivo in the brains of transgenic mice expressing T‐antigen (Tretiakova et al, 1999) and in vitro in a glial cell culture system (Gallia et al, 1998). As Purα regulates the promoter activity of the gene expressing T‐antigen and by associating with T‐antigen, modulates the activity of this protein, we sought to perform a reciprocal experiment to examine the effect of T‐antigen on the Purα promoter and to determine whether association of T‐antigen and Purα affects the ability of Purα to downregulate the Purα promoter in glial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Development of transgenic mice with expression of JCV T‐antigen in brain and the occurrence of hypomyelination which correlated with low level expression of MBP suggested that the interaction of JCV T‐antigen with Purα may have a negative effect on transcription of the MBP promoter. Support for this notion came from studies showing the association of T‐antigen and Purα in mouse brain experiencing demyelination (Tretiakova et al, 1999).…”
mentioning
confidence: 98%
“…In this case, Sp1 in not directly involved in basal expression of JCV genome. Moreover, Tretiakova et al (1999a) demonstrated that Sp1 associated Purα regulates myelin basic protein (MBP) expression, especially during brain development, and that TAg can bind Purα and downregulate MBP transcription (Tretiakova et al, 1999a,b). As a result in oligodendrocytes, JCV may lead to hypomyelination in two distinct ways: utilizing Sp1 for activation of JCV early genes (TAg in particular) and decreasing the level of MBP gene expression through association of T antigen with Purα.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the pur proteins may associate with the BC1 RNP via protein—protein interactions with the Translin, as pur α has been reported to interact with several cellular and viral proteins to perform diverse functions (Johnson et al, 1995; Gallia et al, 1999; Tretiakova et al, 1999 a , b ). Moreover, it was also reported that combinatorial interactions between pur α, pur β, and a Y‐box protein, MSY1, may have functional significance in regulating transcriptional activity of the smooth muscle α‐actin gene (Kelm et al, 1999).…”
Section: Discussionmentioning
confidence: 99%